Review Artikel : KANDUNGAN SENYAWA KIMIA BUAH PISANG DAN BIOAKTIVITASNYA - Nikmah Nuur R; Susanti Susanti; Definingsih Yuliastuti; Wahyunita Yulia Sari (RESEARCH FAIR UNISRI, 2021)
Banana is one of the horticultural commodities with high production and has prospects as an export commodity. Banana is a fruit that is able to grow everywhere, both in villages and cities without seasonality and is easily available in Indonesia so that its production is abundant when nutritious alternative food is used as a source of vitamins, minerals and carbohydrates. This research method uses a literature study. Bananas contain certain active compounds, such as phenols, flavonoids, tannins, glycosides, proanthocyanidins, monoterpenoids and sesquiterpenoids, quinones, terpenoids, saponins, and alkaloids. The benefits of this type of kepok banana include natural antioxidants, antineogenic, antibacterial, vermicidal activity, and a high source of potassium.